An Ultrafast Ultrahigh-Performance Liquid Chromatography Coupled With Tandem Mass Spectrometry Method for Cannabidiol Monitoring in Pediatric Refractory Epilepsy - Pérez Montilla, Carlos Alberto (2021)
Background: Cannabidiol (CBD) is a nonpsychoactive natural product that has been increasingly used as a promising new drug for the management of neurological conditions such as refractory epilepsy. Development of rapid and sensitive methods to quantitate CBD is essential to evaluate its pharmacokinetics in humans, particularly in children. The objective of this work was to develop and validate an ultrafast ultrahigh-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) method for CBD quantitation that is capable of detecting major CBD and tetrahydrocannabinol (THC) metabolites in the plasma of pediatric refractory epilepsy patients.Methods: Eight-point CBD calibration curves were prepared using 60 µL of plasma from healthy volunteers. Samples were analyzed in a Shimadzu Nexera X2 UHPLC system, which was coupled to a Sciex QTRAP 6500 mass spectrometer. Chromatography was optimized in acetonitrile (ACN)/water with a 70%-90% gradient of ACN in 2 minutes. Multiple reaction monitoring transitions of major CBD and THC metabolites were optimized in patient plasma.Results: The optimized UHPLC-MS/MS method was validated for the linear range (1-300 ng/mL) of CBD (r2 = 0.996). The limit of quantification and limit of detection were 0.26 and 0.86 ng/mL, respectively. Accuracy and precision met the acceptable validation limits. CBD recovery and matrix effects were 83.9 ± 13.9% and 117.4 ± 4.5%, respectively. The method was successfully applied to quantify CBD and detect the major CBD and THC metabolites in clinical samples. 7-COOH-CBD was the most intensely detected metabolite followed by glucuronide conjugates.Conclusions: A simple and sensitive method for rapidly monitoring CBD and identifying relevant metabolites was developed. Its applicability in samples from children treated for epilepsy was demonstrated, making it an excellent alternative for performing pharmacokinetic studies.